NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI MEGENGAN DI DESA LANGGENHARJO KECAMATAN JUWANA KABUPATEN PATI - Sinta Nur Azizah; Puspo Nugroho (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2025)
This research aims to describe the implementation and values ​​of Islamic education in the megengan tradition. This type of research uses a qualitative descriptive method with a phenomenological approach. This research took place in Langgenharjo village, Juwana subdistrict, Pati Regency. The data collection methods for this research are observation, interviews and documentation methods. The results obtained from this research are that the implementation of the Megengan tradition is carried out in the month of Sha'ban in the afternoon until dusk at the prayer room by bringing food in the form of blessed rice brought from home which will later be exchanged with other people. The implementation of the megengan tradition begins with an opening, mauidhoh hasanah, tahlil, prayer and closing. The implementation of this tradition is led by religious figures. The values ​​of Islamic education in the Megengan tradition include gratitude, togetherness, tolerance and simplicity. Keywords: Values, Islamic Education, Megengan Tradition